Management of Extensive Subcutaneous Emphysema with Blow Hole Infraclavicular Incision and Continuous Suction Installation - Junaidi, Katerine; Oea Khairsyaf; Russilawati Russilawati; Deddy Herman (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Subcutaneous emphysema often occurs in cases of implanted pneumothorax chest tubes and must always be evaluated. Subcutaneous emphysema is a condition where air or gas is found in the tissue under the skin. Case presentation: A 49-year-old man was treated for sudden shortness of breath that occurred after a violent cough accompanied by pain and heaviness in the chest area 1 day before admission to the hospital. The patient had previously received anti-tuberculosis drug treatment for 6 months based on chest X-ray results in 2022, and the patient had undergone a rapid molecular test (TCM) examination, mycobacterium tuberculosis (Mtb), and obtained Mtb results not detected. Lung auscultation obtains sound intensity breath weakness until it disappears in both lung fields. Palpation of the skin revealed widespread crepitus on the face, neck, upper extremities, back, chest, and abdomen. The range of motion areas of the neck, shoulders, and hands are limited due to pain with movement. Evaluation of the chest tube obtained: the chest tube was installed in the anterior axillary line on the right at the level of the 5th intercostal space with number 10 attached to the chest wall and the chest tube well fixed to the chest wall. The end chest tube has been connected to the WSD bottle, and evaluation of the WSD shows that there are undulations and bubbles. Conclusion: The patient was admitted with spontaneous pneumothorax secondary to tuberculosis and was implanted with a chest tube.